The Effect of Paradoxical leadership on Employee well-being : Mediating Role of Harmonious work passion at Hotel Pangeran Beach Padang - Fadila Azzahra Dila; Hermansyah (Pt. Threeple Herphi Educate, 2026)
This study examines the role of paradoxical leadership in shaping employee well-being by considering harmonious work passion as a mediating variable among employees of Hotel Pangeran Beach Padang. The hospitality industry is characterized by intense job demands, making adaptive leadership and attention to employees’ psychological conditions essential for maintaining service quality and organizational sustainability. Using a quantitative approach with a causal relationship design, this study involved all hotel employees as research participants, resulting in 111 valid responses collected through a five-point Likert scale questionnaire. The data were analyzed using Partial Least Squares–based Structural Equation Modeling (PLS-SEM) with the support of SmartPLS version 4.0. The findings indicate that paradoxical leadership has a direct positive and significant effect on employee well-being and also plays a strong role in enhancing harmonious work passion. However, harmonious work passion does not show a significant influence on employee well-being and does not function as a mediating variable in the relationship between paradoxical leadership and employee well-being. The R-square results further reveal that paradoxical leadership has a very strong explanatory power for harmonious work passion, whereas its contribution to employee well-being remains relatively limited. Overall, this study highlights that employee well-being is more strongly influenced by direct leadership practices than by psychological mechanisms such as work passion. These findings are expected to enrich the literature on leadership and employee well-being and provide practical insights for hotel management in implementing adaptive leadership approaches that prioritize employee welfare.